Les Lumières en Amérique espagnole : plan d’études pour la Colombie coloniale de Moreno y Escandón (1774-1779) - Loncol, Jean-Marie (Man and Nature / L'homme et la nature)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 1984)
Moreno was not vehemently anti-clerical, as some historians have portrayed him. His plan for the reform of colonial education, summarized in this article, was actually very cautious. It failed primarily because of opposition from the Dominicans.